Aspergillus fumigatus proteases, Asp f 5 and Asp f 13, are essential for airway inflammation and remodelling in a murine inhalation model. Issue 5 (16th April 2015) - Namvar, S.; Warn, P.; Farnell, E.; Bromley, M.; Fraczek, M.; Bowyer, P.; Herrick, S.
Summary: Background: In susceptible individuals, exposure to Aspergillus fumigatus can lead to the development of atopic lung diseases such as allergic bronchopulmonary aspergillosis (ABPA) and severe asthma with fungal sensitization (SAFS). Protease allergens including Asp f 5 and Asp f 13 from Aspergillus fumigatus are thought to be important for initiation and progression of allergic asthma. Objective: To assess the importance of secreted protease allergens Asp f 5 (matrix metalloprotease) and Asp f 13 (serine protease) in Aspergillus fumigatus ‐induced inflammation, airway hyperactivity, atopy and airway wall remodelling in a murine model following chronic exposure to secreted allergens. Methods: BALB/c mice were repeatedly intranasally dosed over the course of 5 weeks with culture filtrate from wild‐type (WT), Asp f 5 null (∆5) or Asp f 13 null (∆13) strains of Aspergillus fumigatus . Airway hyper‐reactivity was measured by non‐invasive whole‐body plethysmography, Th2 response and airway inflammation by ELISA and cell counts, whilst airway remodelling was assessed by histological analysis. Results: Parent WT and ∆5 culture filtrates showed high protease activity, whilst protease activity in ∆13 culture filtrate was low. Chronic intranasal exposure to the three different filtrates led to comparable airway hyper‐reactivity and Th2 response. However, protease allergen deleted strains, in particular ∆13 culture filtrate, induced significantly less airway inflammation and remodelling compared to WT culture filtrate. Conclusion: Aspergillus fumigatus ‐secreted allergen proteases, Asp f 5 and Asp f 13, are important for recruitment of inflammatory cells and remodelling of the airways in this murine model. However, deletion of a single allergen protease fails to alleviate airway hyper‐reactivity and allergic immune response. Targeting protease activity of Aspergillus fumigatus in conditions such as SAFS or ABPA may have beneficial effects in preventing key aspects of airway pathology.